Impact of a provider training program on the treatment of children with autism spectrum disorder at psychosocial care units in Brazil - Luciana C. Silva (Brazilian Journal of Psychiatry, 2017)
Objective: To develop, implement, and verify the impact of a training program for health care providers working with children with autism spectrum disorder (ASD) in psychosocial care centers for children and adolescents (Centro de Atenção Psicossocial à Infância e à Adolescência – CAPSi) in São Paulo, Brazil. Methods: This quasi-experimental study was conducted with 14 professionals from four CAPSi units. The training program consisted of six phases: 1) pre-intervention observation; 2) meeting with staff to assess the main needs of the training program; 3) developing materials for training and evaluation; 4) meetings to discuss program implementation; 5) a final meeting for case discussion and evaluation; and 6) distance supervision. Three measures were used to evaluate the training program: i) the Knowledge, Attitudes, and Practices (KAP) questionnaire; ii) videos containing questions designed to assess program comprehension; and iii) a satisfaction survey. Results: Thirteen videos were produced to as visual aids for use during the training program, and a further 26 videos were developed to evaluate it. The program was well evaluated by the participants. The video responses and KAP questionnaire scores suggest that staff knowledge and attitudes improved after training. Conclusion: The positive findings of this study suggest that the tested training program is feasible for use with multidisciplinary teams working in the CAPSi environment.